Small amounts of tissue preserve pancreatic function: Long-term follow-up study of middle-segment preserving pancreatectomy. Issue 46 (November 2016) - Lu, Zipeng; Yin, Jie; Wei, Jishu; Dai, Cuncai; Wu, Junli; Gao, Wentao; Xu, Qing; Dai, Hao; Li, Qiang; Guo, Feng; Chen, Jianmin; Xi, Chunhua; et al.
Abstract : Abstract: Middle-segment preserving pancreatectomy (MPP) is a novel procedure for treating multifocal lesions of the pancreas while preserving pancreatic function. However, long-term pancreatic function after this procedure remains unclear. The aims of this current study are to investigate short- and long-term outcomes, especially long-term pancreatic endocrine function, after MPP. From September 2011 to December 2015, 7 patients underwent MPP in our institution, and 5 cases with long-term outcomes were further analyzed in a retrospective manner. Percentage of tissue preservation was calculated using computed tomography volumetry. Serum insulin and C-peptide levels after oral glucose challenge were evaluated in 5 patients. Beta-cell secreting function including modified homeostasis model assessment of beta-cell function (HOMA2-beta), area under the curve (AUC) for C-peptide, and C-peptide index were evaluated and compared with those after pancreaticoduodenectomy (PD) and total pancreatectomy. Exocrine function was assessed based on questionnaires. Our case series included 3 women and 2 men, with median age of 50 (37–81) years. Four patients underwent pylorus-preserving PD together with distal pancreatectomy (DP), including 1 with spleen preserved. The remaining patient underwent Beger procedure and spleen-preserving DP. Median operation time and estimated intraoperative blood loss were 330 (250–615) min and 800 (400–5500) mL, respectively. Histological examination revealed 3 cases of metastatic lesion to the pancreas, 1 case of chronic pancreatitis, and 1 neuroendocrine tumor. Major postoperative complications included 3 cases of delayed gastric emptying and 2 cases of postoperative pancreatic fistula. Imaging studies showed that segments representing 18.2% to 39.5% of the pancreas with good blood supply had been preserved. With a median 35.0 months of follow-ups on pancreatic functions, only 1 patient developed new-onset diabetes mellitus of the 4 preoperatively euglycemic patients. Beta-cell function parameters in this group of patients were quite comparable to those after Whipple procedure, and seemed better than those after total pancreatectomy. No symptoms of hypoglycemia were identified in any patient, although half of the patients reported symptoms of exocrine insufficiency. In conclusion, MPP is a feasible and effective procedure for middle-segment sparing multicentric lesions in the pancreas, and patients exhibit satisfied endocrine function after surgery.